Сlinical and hemodynamic characteristics and coronary blood flow in patients with chronic coronary artery disease and type 2 diabetes - B. U. Mardanov; M. A. Kokozheva; F. B. Shukurov; B. A. Rudenko; M. N. Mamedov (Российский кардиологический журнал)
Aim. To assess the features of clinical and hemodynamic characteristics and the severity of coronary involvement in patients with chronic coronary artery disease (CAD) with and without diabetes.Material and methods. The study included 100 patients with stable CAD, which were divided into two groups: group I (mean age, 57,9-1,04 years, male/female 35/14) — 49 patients with CAD and type 2 diabetes, II — (60,2-0,9 years, 34/17) — 51 patients without SD. Along with behavioral and biological risk factors, clinical and hemodynamic characteristics were analyzed. All patients underwent coronary angiography.Results. The presence of diabetes in patients with CAD was associated with abdominal obesity and comorbidity of somatic diseases. Among group I patients, electrocardiographic signs of left ventricular hypertrophy, conduction abnormalities, accompanied by a decrease in the left ventricular ejection fraction, impaired diastolic function, and high mean pulmonary artery pressure were significantly more often detected. In patients with CAD and type 2 diabetes, significant right coronary artery (CA) stenoses were more often recorded (39%), while in patients without diabetes, the anterior descending artery was the most susceptible to atherosclerosis. In group I, stenosis of the distal CA third was detected 1,5 times more often (p<0,001), and their diffuse multivessel lesion prevailed by 28% (73% and 45%, respectively, p<0,005). The average SYNTAX score in patients with and without diabetes was 29,2±0,8 vs 22±0,7, respectively (p<0,0005).Conclusion. In patients with CAD and diabetes, more pronounced atherosclerotic coronary involvement (diffuse multivessel CAD) was revealed, which should be taken into account when planning further treatment. The risk of adverse cardiovascular events will always be present with percutaneous coronary interventions.